Cosmological Interpretation: A View of Wind Concept Shi’a Literature - Novizal Wendry (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The debate over the origin of the wind between medieval scientists and theologians became a hot issue. Scientists that consist of philosophers based their arguments on empirical facts and theologians werebased on the revelation of al-Qur’an and Hadith. One of the medieval theologians was al-Majlisī (1037-1110/1627-98). He interpreted cosmological verses based on the process, categorization, and the term of al-Qur'an. This research is a library research usinga historical approach to obtain data and conducting content analysis. As for the term related to the Qur'an about wind, a semantic approach was used. Primary data was the work of al-Majlisī, Biḥār al-Anwar. The results of the study indicated that al-Majlisī rejected the astrological theory which stated that wind is a spin of air originating from the smallest particular composition of the earth, heated, and subjected to evaporation. According to al-Majlisī, the wind caused by God's willin power to blow it with the intensity that He desired. According to al-Majlisī, the wind can be distinguished whether it is beneficial or not as found in al-Qur'an